Funerals against death. (2nd April 2016) - Bailey, Tara; Walter, Tony
Abstract : While anthropological studies in non-Western societies show how funerals protect the community from the threat of death, sociological studies of British funerals have so far focused on meanings for the private family. The article reports on results from a Mass Observation directive – the first British study to focus specifically on the entire funeral congregation – and shows how attendees experience the contemporary life-centred funeral as a symbolic conquest of death. While the eulogy's accuracy is important, even more so – at least for some – is its authenticity, namely that the speaker has personal knowledge of the deceased. Whereas Davies analyses the power of professionally delivered ritual words against death, our data reveals how admired is the courage exercised by non-professionals in speaking against death, however faltering their words. Further, the very presence of a congregation whose members have known the deceased in diverse ways embodies a configurational eulogy, which we term relationships against death. We thus argue that funerals symbolically conquer death not only through words delivered by ritual specialists, but also through those who knew the deceased congregating and speaking .